Stratigraphic revision of the Eocene-Pliocene intermontane San Antonio de los Cobres Basin, Puna Salteña, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The intermontane San Antonio de los Cobres basin (SAC), is located in the Eastern border of the Puna, near the limit with the Eastern Cordillera (Ramos, 2017). This basin preserves the stratigraphic record of the Salta Group (Cretaceous-Eocene) and the Andean foreland (Eocene -Pliocene). This basin has been the subject of numerous investigations mainly focused on structural and volcanic aspects (e.g. Viramonte et al., 1994; Petrinovic et al., 1999; Riller et al., 2001; Petrinovic et al., 2005; Norini et al., 2013; Seggiaro et al., 2016). However, there are few works concerning to the sedimentary sequences, which have led to a lack of consensus on the stratigraphic record. Nevertheless, this basin is of special interest since it is located in a singular position at the limit of the Puna and the Eastern Cordillera, so that the sedimentary record archives the moment and the way in which this area evolved.In this contribution we present an integrated stratigraphic column for the San Antonio de los Cobres basin based on detailed cartography, stratigraphic relationships, sedimentological characterization and available ages. Likewise, and in accordance with the norms and recommendations of the Argentine Stratigraphy Code (1992), we propose a new lithostratigraphic unit, which allows organizing the stratigraphy of the Miocene record.The basement of this basin is composed mainly of metamorphic and metasedimentary rocks of Lower Proterozoic - Lower Paleozoic age (e.g. Puscovicana Formation - Ramos (1973), Donato and Vergani (1988), Guayoc Chico Group – Ramos (1970), Parcha Formation - Harrington y Leanza, (1957)) and intrusive igneous rocks (granodiorites and rhyodacitic porphyries) corresponding to the Oire Eruptive Complex (Middle - Upper Ordovician) (Turner, 1960). These units are exposed, in general, in ranges-limiting the basin.The sedimentary succession of the Cretaceous - Eocene age corresponding to the Salta Group rift related basin lies unconformably on the basement rocks (Turner, 1959). These units maintain the lithological characteristics described for the rest of the basin, in particular with the deposits of the Alemanía and Tres Cruces sub-basins (Salfity and Marquillas, 1994).The foreland basin is characterized by sandy to conglomeratic rocks, which have been deposited in different continental depositional systems, intercalated with volcanic deposits. The oldest unit that is recognized is the Geste Formation (Turner, 1960; Alonso, 1992). It is identified by the up-wards coarsening pattern and light gray-pink colors. Main outcrops can be found in the area of Corte Blanco and Quebrada Los Patos (Fig. 1d), in the southeastern sector of the basin at the foot of the Muñano mountain range (Fig. 1b - Quebrada Fundiciones), and in the Piscuno area (Fig. 1c). Based on differences in facies associations, three informal sections were distinguished: a) the lower section is characterized by a succession of reddish pelitic layers with sporadic intercalations of tabular banks composed of carbonate pisolites (Fig. 3c). Upwards it passes to tabular layers of claystones, silty claystones and silty sandstones with calcareous nodules and rhizoconcretions; alternating with tabular to lenticular sandy to conglomeratic layers. This section is limited in its top by a hardened calcareous horizon, approximately six meters thick (Fig. 3e); b) the middle section is composed mainly of sandy to conglomeratic facies to the bottom (Fig. 3f) and pebbly to cobbly conglomerates at the top (Fig. 3g) with lenticular geometry, which intercalate with tabular strata of clayey siltstones and silty sandstones facies. The presence of greenish-yellow limestone clasts is highlighted, which suggest the uplift and exhumation of the Yacoraite Formation (Fig. 3h); c) the upper section is made up of tabular to slightly lenticular, pebbly to bouldery, clast-supported and imbricated conglomerates (Fig. 3i). At the moment, this Formation lacks absolute age determination in the study area. By similarity and correlation with the exposed outcrops in the adjacent Pastos Grandes basin, we assume ages between 37 - 35 Ma (DeCelles et al., 2007).The Conglomerado Los Patos lies on angular unconformity over different units of the Santa Bárbara Subgroup (Fig. 3j, k) and/or on the Geste Formation (Fig. 3d). It is composed by cobbly to bouldery, matrix-supported conglomerates, clast-supported conglomerates and conglomerates with imbricated clasts. A maximum depositional age of 14.5 ± 0.5 Ma is constrained by U-Pb zircon dating in a volcanic clast contained in the base of the unit (del Papa and Petrinovic, 2017) while the top is limited at 13 Ma of the Viscachayoc Ignimbrite (Petrinovic et al., 1999).The sedimentary succession above the Vizcachayoc Ignimbrite and below the Pleistocene – Holocene deposits has been named San Antonio de los Cobres Formation by Pingel et al., (2019). In the present work, we proposed the formal assignation complemented by stratigraphic details and sedimentological descriptions. Based on distinctive sedimentary facies associations, this Formation is divided into two formal members: a) Corte Blanco Member (Nom. Nov.): it lies unconformably on the Conglomerado Los Patos (Fig. 3k), on the Vizcachayoc Ignimbrite, or on the Geste Formation. It is characterized by a basal eruptive unit known as “Corte Blanco Ignimbrite” (Nom. Nov. for Toba I of Viramonte et al., 1984). Above, it develops an aeolian and fluvio-aeolian succession (Figs. 4, 5b) composed of sets of sandstones, with tabular cross-stratification and large-scale trough/ tabular cross-stratification. The top is defined by the eruptive unit “Ignimbrita Ramadas” (Nom. Nov. for Tufita Corte Blanco - Viramonte et al., 1984) (Figs. 4, 5a). U-Pb zircon dating in both eruptive units allows us to constraint the age of this Member between 6.4 and 7.8 Ma (Late Miocene); b) Muñano Member (Nom. Nov.): it lies in sharp and concordant relation on Corte Blanco Member. It is characterized by a coarsening upward sequence. It begins with a succession of well-channelized sandstone bodies, intercalated with fine to medium conglomeratic beds. In the medium section predominates levels of multi-layering conglomerates intercalated with medium to coarse sandy beds; while the uppermost section consists of medium to coarse-grained sandy levels with erosive bases (concave) and thin lenses of pebbly conglomerate, and thick bodies of clast-supported, pebbly to bouldery conglomerates towards the top. U-Pb zircon dating yielded an age of 5.5 Ma in volcanic ash fall contained at the upper section (Pingel et al., 2019), so a Late Miocene – Pliocene? age could be assigned to this Member.
Keywords: Andean Foreland, Intermontane Basin, Geste Formation, San Antonio de los Cobres Formation, Puna.